2016
DOI: 10.3390/toxins9010014
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical Basis of Paradoxical Masseteric Bulging after Botulinum Neurotoxin Type A Injection

Abstract: The aim of this study was to determine the detailed anatomical structures of the superficial part of the masseter and to elucidate the boundaries and locations of the deep tendon structure within the superficial part of the masseter. Forty-four hemifaces from Korean and Thai embalmed cadavers were used in this study. The deep tendon structure was located deep in the lower third of the superficial part of the masseter. It was observed in all specimens and was designated as a deep inferior tendon (DIT). The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 22 publications
(25 reference statements)
3
51
0
1
Order By: Relevance
“…A recent study discovered a tendinous structure located in the deeper part of the superficial masseter muscle layers in all cadaver specimens examined. This structure, called the deep inferior tendon (DIT), may play a role in the blockage of toxin diffusion from the deep layer to the superficial layer, leaving the latter unaffected by toxin activity and eventually leading to overcompensation from decreased jaw strength . According to the author's experience, if this side effect does not recover within 2 weeks, patients should receive a more superficial booster dose in order to correct the phenomenon …”
Section: Resultsmentioning
confidence: 99%
“…A recent study discovered a tendinous structure located in the deeper part of the superficial masseter muscle layers in all cadaver specimens examined. This structure, called the deep inferior tendon (DIT), may play a role in the blockage of toxin diffusion from the deep layer to the superficial layer, leaving the latter unaffected by toxin activity and eventually leading to overcompensation from decreased jaw strength . According to the author's experience, if this side effect does not recover within 2 weeks, patients should receive a more superficial booster dose in order to correct the phenomenon …”
Section: Resultsmentioning
confidence: 99%
“…The deep and middle layers of the masseter are almost vertical in direction and contraction, while the superficial layer originates more medially on the zygomatic bone, creating an oblique direction of contraction (Figure ), and many cases of paradoxical bulging will take this form. A recently published study discovered a tendinous structure located in the deeper part of the superficial masseter layer in all cadaver specimens examined, which may block toxin diffusion from the deep layer to the superficial layer, making overcompensation more common …”
Section: Incidence Of Complicationsmentioning
confidence: 99%
“…Anatomy textbooks generally describe most of the masseter muscle as being formed by the muscle belly (Standring, ). However, it is reported that the superficial part of the masseter muscle comprises not only the muscle belly but also a strong tendon structure within the muscle belly in the inferior region of the muscle (Lee et al, ). Previous anatomical studies have further revealed that the masseter muscle possesses lamella‐like structures and dense and tough aponeurosis that divide the muscle into separate layers (Gaudy et al, ; Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on an anatomical study, Lee et al proposed mechanisms for this side effect, which may occur because of a broad tendon structure called the deep inferior tendon (DIT) being located within the superficial part of the masseter muscle. This tendon would act like a window that restricts the diffusion of BoNT into the entire masseter muscle (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%